Al-Mahżūrāt al-Lughawiyyah fi Waśāil al-Tawāśul al-Ijtimā’ī wa Aśruhā al-Salbī ala Fasād Akhlāq al-Syabāb fi al-‘Ālam al-Islāmī (Linguistic Taboos in Social Media and Their Negative Impact on Deterioration of Morals of the Youth in the Islamic World) - Ibrahima Aliyu Yunus; Muhammad Isnan Sulaiman (Loghat Arabi : Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2022)
تدور فكرة هذا المقال المعنون بــــ"المحظورات اللغوية في وسائل التواصل الاجتماعي وأثرها السلبي على فساد أخلاق الشباب في العالم الإسلامي" في إلقاء الضوء على ما تقوم به الأفراد والجماعات والفرق في وسائل التواصل الاجتماعي من الأقوال المخالفة للقيم السليمة والحياء العام وما تسببه من انتشار أنواع مختلفة للكلام البذيئ الفاحش (المحظور اللغوي) الذي يخدش الحياء العام ويخالف العادات والأديان والتقاليد للمجتمعات البشرية ذات الفطرة السليمة، وأثرها السلبي على تدمير أخلاق الشباب المسلم. وقد انتهج الباحثان المنهج الوصفي في معالجة الظاهرة. واختتم المقال بخاتمة تنطوي على أهم النتائج التي توصل إليها الباحثان.ABSTRACT The idea of this article entitled “Linguistic Taboos in social media and their negative impact on deterioration of morals of the youth in the Islamic world” revolves around shedding light on the statements made by individuals, groups and teams on social media that contradict sound values and public modesty; which cause the spread of various types of obscene and obscene speech (Linguistic Taboo) that violate public modesty and violate the customs, religions and traditions of human societies with common sense, and their negative impact on destroying the morals of Muslim youth. The researchers adopted the descriptive method in addressing the phenomenon. The article concluded with a conclusion that includes the most important findings.